Evidence suggesting that Homo neanderthalensis contributed the H2 MAPT haplotype to Homo sapiens. (1st August 2005) - Hardy, J.; Pittman, A.; Myers, A.; Gwinn-Hardy, K.; Fung, H.C.; de Silva, R.; Hutton, M.; Duckworth, J.
Abstract : The tau ( MAPT ) locus exists as two distinct clades, H1 and H2. The H1 clade has a normal linkage disequilibrium structure and is the only haplotype found in all populations except those derived from Caucasians. The H2 haplotype is the minor haplotype in Caucasian populations and is not found in other populations. It shows no recombination over a region of 2 Mb with the more common H1 haplotype. The distribution of the haplotype and analysis of the slippage of dinucleotide repeat markers within the haplotype suggest that it entered Homo sapiens populations between approx. 10000 and 30000 years ago. However, sequence comparison of the H2 haplotype with the H1 haplotype and with the chimp sequence suggests that the common founder of the H1 and H2 haplotypes was far earlier than this. We suggest that the H2 haplotype is derived from Homo neanderthalensis and entered H. sapiens populations during the co-existence of these species in Europe from approx. 45000 to 18000 years ago and that the H2 haplotype has been under selection pressure since that time, possibly because of the role of this H1 haplotype in neurodegenerative disease.